2020
DOI: 10.1007/s13762-020-02729-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of leachate biological treatment using bacteriological and parasitological monitoring

Abstract: Leachate of the uncontrolled landfill contains pollutants, which is discharged directly into the environment. The main objective of this study is to evaluate the reduction of bacteriological and parasitological risks by four biological treatments: sequencing batch reactor, anaerobic, intensive aeration and combination of the three processes. The results showed high bacteriological pollution in the raw leachate: 1.12 × 10 7 CFU/ml, 6.7 × 10 6 and 5.26 × 10 4 for total coliforms, faecal coliforms and Streptococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The concentration of the latter is similar to that found in the slaughterhouse water (0.10 mg/l), but it is lower than that of the wastewater of the direct discharges of the city of Salé (2.93 mg/l) (Boughou et al, 2006). The orthophosphate concentration in the leachate is lower than that of the leachate of the Agadir landfill (172.3 mg/l) (Mherzi et al, 2020). The nitrate concentration remains higher in the leachate (3.1 mg/l) than in the wastewater (0.1 mg/l) and in the M1 mixture (0.2 mg/l).…”
Section: Fig 1: Concentration Log Of Fc and Fsmentioning
confidence: 73%
See 1 more Smart Citation
“…The concentration of the latter is similar to that found in the slaughterhouse water (0.10 mg/l), but it is lower than that of the wastewater of the direct discharges of the city of Salé (2.93 mg/l) (Boughou et al, 2006). The orthophosphate concentration in the leachate is lower than that of the leachate of the Agadir landfill (172.3 mg/l) (Mherzi et al, 2020). The nitrate concentration remains higher in the leachate (3.1 mg/l) than in the wastewater (0.1 mg/l) and in the M1 mixture (0.2 mg/l).…”
Section: Fig 1: Concentration Log Of Fc and Fsmentioning
confidence: 73%
“…The nitrate concentration remains higher in the leachate (3.1 mg/l) than in the wastewater (0.1 mg/l) and in the M1 mixture (0.2 mg/l). For the wastewater, the nitrate concentration remains lower than that of the slaughterhouse water (2.65 mg/l) and that of the Agadir landfill leachate (62 mg/l) (Mherzi et al, 2020;Boughou et al, 2006). The pretreated wastewater has a lower suspended matter load (0,049g/l) than the leachate (1.771 g/l) and the M1 mixture (0.256 g/l), this result is lower than that found for Tiflet city wastewater (0.282 g/l) and Rabat slaughterhouse wastewater (1.068 g/l) (Qoutbane et al, 2020;Boughou et al, 2006).…”
Section: Fig 1: Concentration Log Of Fc and Fsmentioning
confidence: 98%
“…The visualization of the identification of rhizobacteria showed the association of bacteria from leachate and soil. Several general bacteria present in landfill leachate include Bacillus, Salmonella, Citrobacter, Agrobacterium, Enterobacter, Pseudomonas, Staphylococcus, and Enterococcus [ 37 , 45 , 83 ]. Naturally, bacteria in soil and plants are generally the Naturally, bacteria in soil and plants are generally the genus Bacillus, Acetobacter, Actinobacteria, and Pseudomonas , are in media with high pollutants because they can form spores and produce various enzymes [ 1 , 9 , 136 , 158 ].…”
Section: Resultsmentioning
confidence: 99%
“…These wastes are often described as biohazardous materials that have to be immediately disposed of and treated, due to the presence of infectious bacteria or viruses, and harmful substances that cause further health and environmental damages. Several studies reported that a number of pathogenic bacteria had been detected in the commercial general and medical landfills (Grisey et al, 2010;Mherzi et al, 2020;Yang et al, 2017). Bacteriological pollution such as faecal coliforms, Streptococci and also parasites of intestinal roundworms, for example, Enterobius vermicularis, Ascaris lumbricoides, Trichuris and Hymenolepis nana is found in the raw leachate, which pose a risk for the environmental safety and human health (Mherzi et al, 2020).…”
Section: Medical Textile Waste Landfills: Health and Environmental Im...mentioning
confidence: 99%
“…Several studies reported that a number of pathogenic bacteria had been detected in the commercial general and medical landfills (Grisey et al, 2010;Mherzi et al, 2020;Yang et al, 2017). Bacteriological pollution such as faecal coliforms, Streptococci and also parasites of intestinal roundworms, for example, Enterobius vermicularis, Ascaris lumbricoides, Trichuris and Hymenolepis nana is found in the raw leachate, which pose a risk for the environmental safety and human health (Mherzi et al, 2020). However, a report mentioned that an increase in bacterial mortality had been observed along with the waste age and leaching time (Ware, 2004).…”
Section: Medical Textile Waste Landfills: Health and Environmental Im...mentioning
confidence: 99%